A New Method for Selecting the Phase and Group Velocity Dispersion Curves of Rayleigh and Love Surface Waves: Real Data Case of Central Anatolia, Turkey (Türkiye) - Özcan Çakir; Yusuf Arif Kutlu (MO.RI Publishing, 2023)
We propose a new method to select the dispersion curve of Rayleigh and Love surface waves obtained from local and regional earthquakes. This method is efficient for the crustal tomography studies and the Central Anatolia is chosen to test it. The single-station method utilizing both seismograms and accelerograms is used for the group velocities from local earthquakes while the two-station approach utilizing the cross correlograms is employed for the group and phase velocities using both local and regional earthquakes. The proposed method is made of two stages. The first stage based on the multiple filter technique – MFT is designed for an automatic selection of the desired dispersion curve. In case of the single-station approach, the MFT diagrams are computed for both Rayleigh and Love seismograms or accelerograms. An algorithm based on several selection criteria is employed to extract the corresponding group velocity dispersion curve from the MFT diagram. In case of the two-station method, the MFT diagrams are computed for both Rayleigh and Love cross correlograms. The latter algorithm developed for the MFT diagram is again applied to the cross correlogram to select the respective two-station group velocity dispersion curve. To select the corresponding two-station phase velocity dispersion curve, another algorithm is developed where the joint inversion of phase and group velocities is employed. The RMS value quantifying the misfit between the selected and inverted dispersion curves is found minimum when the selected phase velocity curve is compatible with the group velocity curve extracted via the MFT. The selection procedures defined up until this point constitute the first stage. In the second stage, phase and group velocity gathering around base pathways is performed. This way it is possible to compute the averages and standard deviations for the observed pathways traversing the similar geology. The outliers determined by using the averages and standard deviations are eliminated from the data set and this elimination is performed for phase and group velocities, separately.